PANDANGAN DAN SIKAP MASYARAKAT MENGHADAPI KEMATIAN - Dewi Anggariani; Marhani Malik (SOSIORELIGIUS, 2021)
Death is a mystery that is given different attention in every society based on religion and beliefs held in its culture. The diversity of treatment in the event of death is believed to be a reflection of the views of individuals and society in understanding death. This study aims to answer the question: How do people view death and the nature in which humans live after death? and What is the attitude of the community in dealing with the death of their family? The research was conducted in Makassar City with a qualitative research type with an emic approach. Sources of data obtained by in-depth interview techniques, and observation. Study of literature/documents as secondary data by tracing the relevant literature. Meanwhile, data processing and analysis techniques were carried out along with data collection, through data reduction based on the topic of discussion, presenting data in a narrative manner and drawing conclusions. Based on this research, it is known that death is seen as an event of separation between spirit and body and death will surely come, there are those who understand that death is the end of everything but there are those who understand that death is not the end of everything who will be resurrected in the afterlife to take responsibility. deeds in the world. The afterlife is the one to go to after death by going through several processes, and is considered an eternal place. There are different views of the community on the process of accountability in the hereafter to go to the provided nature. People's attitudes in facing death are influenced by the ultimate goal of life to be achieved, and their attitude towards the dead is related to the condition of their relationship with the dead during their lifetime.Death is a mystery that is given different attention in every society based on religion and beliefs held in its culture. The diversity of treatment in the event of death is believed to be areflection of the views of individuals and society in understanding death. This study aims toanswer the question: How do people view death and the nature in which humans live afterdeath? and What is the attitude of the community in dealing with the death of their family?The research was conducted in Makassar City with a qualitative research type with an emicapproach. Sources of data obtained by in-depth interview techniques, and observation. Studyof literature/documents as secondary data by tracing the relevant literature. Meanwhile,data processing and analysis techniques were carried out along with data collection, throughdata reduction based on the topic of discussion, presenting data in a narrative manner anddrawing conclusions. Based on this research, it is known that death is seen as an event ofseparation between spirit and body and death will surely come, there are those whounderstand that death is the end of everything but there are those who understand thatdeath is not the end of everything who will be resurrected in the afterlife to takeresponsibility. deeds in the world. The afterlife is the one to go to after death by goingthrough several processes, and is considered an eternal place. There are different views of thecommunity on the process of accountability in the hereafter to go to the provided nature.People's attitudes in facing death are influenced by the ultimate goal of life to be achieved,and their attitude towards the dead is related to the condition of their relationship with thedead during their lifetime